EVALUATION OF THE BIOLOGICAL EFFECT SYNTHESIZED IRON OXIDE NANOPARTICLES ON ENTEROCOCCUS FAECALIS - kamel, R. M.; Yaaqoob , L. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to demonstrate the biosynthesis procedure of iron oxide nanoparticles (Fe2O3 NPs) by using prodigiosin pigment produced from environmental isolate Serratia marcescens as a reducing and stabilizing agent. Additionally, the synthesis conditions were precisely taken into consideration as a pH of 7 and a temperature of 50°C alongside a concentration of prodigiosin of 12 mg/ml with a precursor of ferric sulfate of 5 mg/50ml in deionized distilled water (DDW). Biosynthesized Fe2O3 nanoparticles have presented many applications such as catalysis, biosensing, anticancer, and biomedical, etc. The study of optimum condition for the synthesis of Fe2O3 was characterized by different techniques, such as (XRD, UV-VIS, AFM, FTIR and FE-SEM). The wavelength of biosynthesis of Fe2O3 by using UV-VIS is (284 nm), Image FE-SEM displays Spherical Fe2O3 NPs in nano-cluster form and the average volume is (35.01) nm). And the effect of Fe2O3 NPs on bacteria Enterococcus faecalis on an inhibition zone 31 mm.